How do various encapsulation techniques improve the oral delivery of food protein hydrolysates? - Seid Reza Falsafi; Sneh Puniabangar; Monica Trif; Katarzyna Samborska; Alicja Barańska; Basheer Aaliya; Kappat Valiyapeediyekkal Sunooj; Merve Tomas; Esra Capanoglu; Hadis Rostamabadi (Food Frontiers)
Abstract The development of bioformulations based on food protein hydrolysates (FPHs) has gained significant traction in the food and pharmaceutical sectors due to their biophysical and biochemical properties, including health‐promoting effects, biocompatibility, and biodegradability. However, the oral delivery of FPHs presents notable technical challenges, largely due to their inherent limitations such as (bio)stability, permeability, bioavailability, and molecular size. This review provides a comprehensive overview of FPHs, including their structural characteristics, origins, methods of preparation, and associated health benefits. Additionally, it highlights the challenges related to their oral delivery. Recent advancements in the formulation and delivery of FPHs through biopolymeric controlled release systems—such as micro‐ and nanoparticles, hydrogels, biofunctional films and composites, and electrospun fibers—are discussed. We also explore lipid‐based delivery platforms, including liposomes, chitosomes, emulsions, Pickering emulsions, nanostructured lipid carriers, solid lipid nanoparticles, and surfactant‐based carriers. Furthermore, this article emphasizes the importance of controlled delivery and targeted release of FPHs following oral administration. The challenges in designing effective lipid/biopolymer‐based carriers for FPHs, along with future prospects and opportunities in this growing field, are also thoroughly examined.